PENGEMBANGAN MEDIA ULAR TANGGA PADA MATERI PENJUMLAHAN DAN PENGURANGAN KELAS I UPT SDN 13 GRESIK - Mega Putri Permatasari; Ismail Marzuki (STKIP Subang, 2022)
This study aims to develop a snake and ladder game media to improve elementary school students' learning outcomes in addition and subtraction concepts. One of the problems of education is the lack of media facilities and infrastructure, so teachers are required to be creative in improving the quality of learning in the classroom, such as developing learning media in the classroom. One of the interesting learning media that can overcome student boredom in learning activities is game-based learning activities, such as the application of snakes and ladders game media. In student learning outcomes, it shows that 10% of students have scores above the KKM before applying the snake and ladder learning media, while after applying the snake ladder game learning media, 100% of students have scores above the KKM (Minimum Completeness Criteria), it shows that student learning outcomes have increased. 90%. The use of learning media in learning activities makes it easier for students to gain understanding and motivate students to learn.